Degradation of Phenanthrene and some selected Petroleum Hydrocarbons by Lysinibacillus fusiformis (ALSL 5): Article Retracted by the Authors - Ifeoluwa, Soyoye Emmanuel; Theophilus, Temiloluwa Esther; Ogunware, Adedayo Emmanuel; Oyende, Yetunde Ebunlomo; Onakomaiya, Adedayo Olawale (Journal of Experimental Sciences, 2020)
Polycyclic aromatic hydrocarbons (PAHs) are universal environmental contaminants of great concern with regard to their potential exposure and deleterious effect on human health. This study was conducted to determine phenanthrene and other PAHs degradation activity of Lysinibacillus fusiformis . The biodegradation study was analyzed by Gas Chromatography-Flame Ionization Detector (GC-FID) and the result showed that the isolate was able to degrade 57 %, the rate of degradation was 6.126 mg/l/day, the rate of degradation constant was 0.0085 /day and the half-life was 8.0975 days in the selective medium within days 10. Lysinibacillus fusiformis, ALSL 5 also showed activities on the other PAHs it was tested on. The results revealed that Lysinibacillus fusiformis, ALSL 5 was able to degrade phenanthrene significantly and it could prove to be promising bacteria for bioremediation of PAH-containing pollutant from the contaminated site.